ANALISIS PENERAPAN METODE ACTIVITY BASED COSTING UNTUK PENETAPAN BIAYA KAMAR RAWAT INAP RSUD KOTA DUMAI - Desi Ratna Sari; Kirmizi -; Enni Savitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study purpose to determine Activity Based Costing (ABC) toward hospitalization costing in Dumai General Hospital. Hospital is a service company whose orientation is non-profit; therefore the accuracy of management is required in taking decision especially in determination of hospitalization cost. The problem of this study is how to determine hospitalization cost in Dumai General Hospital by using ABC methods. The data used in this study were primary data from interview result and secondary data from the hospital’s financial report related to this study. Data collection techniques were done by collecting the documents from financial reports as well as data related to the object of research and conducted interview with leader and employees asociated with necessary data in this study. ABC methods assessed can provide more accuracy than with traditional methods in calculating the hospitalization cost that can assist management in determining hospitalization cost according to the facilities in each class of hospitalization. In this study, cost driver used in the calculation of hospitalization costing consisted of the number of day hospitalization, number of patients, power consumption and space of hospitalization room. Result of the calculation using ABC method in Dumai General Hospital for hospitalization cost showed that the cost charged by activities that occurred in each room according to the facilities given by hospital at standard level of hospitalization.Keywords: Analyze, Costing, Hospitalization, and Rates